Permeation measurement of 27 chemotherapy drugs after simulated dynamic testing on 15 surgical and examination gloves: A knowledge update. (August 2021) - Nalin, Marie; Hug, Guillaume; Boeckmans, Eric; Machon, Christelle; Favier, Bertrand; Guitton, Jérôme
Purpose: Exposure to anticancer drugs is one of the known risks for people working in specialist oncology units. Wearing gloves is a vital form of personal protection. The aim of this study was to assess, in close to real use dynamic conditions, the permeability of 15 surgical and examination gloves made from different materials when exposed to 27 anticancer drugs included in the list from international Guides and Recommendations. Methods: Gloves were tested by using controlled dynamic conditions replicating flexion and extension movements that mimic typical clinical applications. Tests were performed at 37°C or at 43°C for 30 min and anticancer drugs were tested at the highest concentration used in clinical practice. To determine the permeation rate, the quantification of anticancer drugs was performed with selective and sensitive analytical methods such as inductively coupled plasma-mass spectroscopy and liquid chromatography-mass spectrometry. Results: All the gloves met the EN 16523-1 European standard (1000 ng/(min.cm 2 )). The penetration rate of busulfan, carmustine and thiotepa exceeded the ASTM D-6978-05 American standard (10 ng/(min.cm 2 )) with several surgical and/or examination gloves. This standard was met in all of cases when double gloving was used. Breakage of several nitrile gloves was observed in relation with the excipient used by drugs suppliers. Conclusions: Permeation is a complex multifactorial phenomenon. However, we have suggested that the thickness of the glove and three physicochemical parameters (molecular weight, topological polar surface area and hydrogen bond donor) of the drug were the main parameters affecting permeation.